Comparison of Efficiency in Cash and Future Market of Gold Coin - Mahdi Eskandari (University of Tehran, 2021)
Objective: According to the efficient market hypothesis, market efficiency refers to the condition in which prices in the markets are adjusted immediately to the new information. The speed and quality of response to new information determine the level of market efficiency. The lower speed and quality will result in lower efficiency. The weak level of market efficiency is a condition in which the price of an asset is predictable with publicly available information. In another word, prices are following a predictable pattern and not moving based on the random walk hypothesis. This study compares and evaluates a weak level of efficiency in future and spot market of gold coins. Methods: This study examines gold coin transactions and the efficiency of future contracts in various futures and cash markets. By using the daily return of gold coins from 2008 to 2018 and R software, the paper examines the weak form of efficiency through random walks and martingale difference sequence hypotheses. Results: Using 10 year period data from 2008 to 2018 demonstrates inefficiency in all markets. However, compared to the other markets, the cash coin market has a relatively higher level of market efficiency. We found that there is an indirect relationship between the term of the contract and its efficiency. The weak form efficiency of the contracts is lower in the future contracts with a longer term to maturity. The probability of rejecting the weak form of efficiency is higher in futures markets. Conclusion: Considering a higher level of weak efficiency in the cash market (in comparison with the future markets) and the indirect relationship between the term of the contract and the level of efficiency, investors are encouraged to focus on the gold coin cash market. Price changes in the cash market are less predictable than in other markets. As a result, this market is recommended for passive investors who buy and hold the asset.